DALK combined intralamellar tectonic patch graft: an alternative approach to treat frank corneal perforation - Gege Xiao; Hanzhi Ben; Shaofeng Gu; Jing Hong (BMC Ophthalmology, 2023)
Abstract Background Deep anterior lamellar keratoplasty (DALK) has gained popularity in cases of corneal thinning and leaking descemetocele. In this study, we introduced an intralamellar tectonic patch graft in addition to conventional DALK procedures to treat frank cornea perforation. Methods This retrospective case series included 13 patients (13 eyes) with frank corneal perforations who underwent DALK combined with intralamellar tectonic patch graft between December 2015 and December 2021. In addition to the standard DALK procedure, the perforation site was repaired with an extra intralamellar tectonic patch graft. The collected data included patient demographics, aetiology, size and location of the corneal perforation, visual acuity, surgical details, and postoperative complications. Results Seven patients underwent autologous intralamellar patch grafts, whereas six received allogeneic ones. Anatomical success was achieved in all patients. The mean postoperative follow-up was 33.31 ± 25.96 months (6–73 months). The postoperative visual acuity (0.90 ± 0.65 logMAR) was significantly improved (P = 0.003) compared to the preoperative score (1.74 ± 0.83 logMAR). Best corrected visual acuity (BCVA) improved in 12 eyes (92.3%). The mean endothelial cell density was 2028 ± 463 cells/mm2, 6–12 months postoperatively. There was no recurrence of perforation, and the anterior lamellar graft remained transparent in 12 patients (92.3%). Postoperative complications included epithelial defects (23.1%), ocular hypertension (15.4%), and cataract (7.7%). Conclusions DALK combined with intralamellar tectonic patch graft may serve as a secure and effective alternative in treating frank corneal perforation, with reduced complications compared to conventional penetrating keratoplasty.